2020
DOI: 10.1108/pr-05-2019-0262
|View full text |Cite
|
Sign up to set email alerts
|

Shared leadership and team creativity

Abstract: PurposeThe purpose of this paper is to extend the theoretical understanding and conceptualization of shared leadership by examining the impact of cognitive trust as an antecedent of shared leadership. Further, the study examines the mediating effect of team learning on relationship between shared leadership and team creativity.Design/methodology/approachThe study adopted a mixed method approach with sequential explanatory research strategy. Using a survey questionnaire, data from 44 teams were collected at two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 72 publications
(94 reference statements)
2
21
0
Order By: Relevance
“…In terms of performance outcomes, follower-level outcomes of creative and innovative behaviour, knowledge management activity and task performance are commonly studied (Palvalin et al , 2017). At the team level, there is emphasis on team performance (Lee et al , 2014; Sandvik et al , 2018; Storm and Scheepers, 2019), team creativity (Tu et al , 2019; Lyndon et al , 2020), team effectiveness (Leuteritz et al , 2017), and project quality and performance (Keller, 1992). At the organisational level, organisational performance (Kehoe and Collins, 2017, Singh et al , 2019a), turnover (Joo, 2010), knowledge management activity (Xiaojun 2017), innovation (Lakshman and Rai, 2019) and financial performance (Berraies and El Abidine, 2019) have been investigated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of performance outcomes, follower-level outcomes of creative and innovative behaviour, knowledge management activity and task performance are commonly studied (Palvalin et al , 2017). At the team level, there is emphasis on team performance (Lee et al , 2014; Sandvik et al , 2018; Storm and Scheepers, 2019), team creativity (Tu et al , 2019; Lyndon et al , 2020), team effectiveness (Leuteritz et al , 2017), and project quality and performance (Keller, 1992). At the organisational level, organisational performance (Kehoe and Collins, 2017, Singh et al , 2019a), turnover (Joo, 2010), knowledge management activity (Xiaojun 2017), innovation (Lakshman and Rai, 2019) and financial performance (Berraies and El Abidine, 2019) have been investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Advances in research have appeared in management journals and across allied disciplines, including education (e.g. Hempsall, 2014, Lyndon et al , 2020; Robert and You, 2018), but research remains fragmentary. Third, there are currently many proposed leadership structures for effectively influencing KW outcomes, but most of which are yet to be reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…The members of non-formal teams who were interviewed advocated that the non-formal leaders should be deliberate about building trust by taking structured action, actively displaying trust and displaying and encouraging openness. The importance of trust is supported by several authors who identified trust as an antecedent of shared leadership (Klasmeier & Rowold, 2020;Lyndon et al, 2020;Seshadri & Elangovan, 2019;Sweeney et al, 2019;Zhu et al, 2018).…”
Section: Trust Buildermentioning
confidence: 93%
“…Thus, team members are motivated to collaborate and help each other in idea generation, selection, and finally idea implementation. That is shared leadership supports creativity and innovation in teams (Lyndon, Pandey & Navare, 2020). Moreover, the link between shared leadership and team innovation is studied by previous researchers (Hoch, 2013; Peter, Braun & Frey, 2015).…”
Section: Theoretical Background and Research Hypothesesmentioning
confidence: 99%